Sistem Pendukung Keputusan Kelompok untuk Penentuan Lokasi Usaha menggunakan Metode Fuzzy SAW Borda - Standy Oei (Ikatan Ahli Informatika Indonesia (IAII), 2020)
The economic development of a city is marked by the increasing number of established businesses. Inaccurate decision about business location can result in losses for the owner. To support proper decision making, various decision making methods have been developed. For example, by using Fuzzy, Analytical Hierarchy Process (AHP), Promethee, Simple Additive Weighting (SAW), Borda, and Hybrid (a combination of several methods). In this research, the author tries to solve the problem of decision making in determining business location, by designing a decision support system that uses a hybrid method approach, a combination of Fuzzy, Simple Additive Weighting (SAW), and Borda. There are 3 alternative locations (A1, A2, and A3), 5 decision makers, and 5 assessment criteria used, such as land eligibility (benefit), population density (benefit), traffic jam (benefit), completeness of files (benefit), and flood intensity (cost). The Decision Support System accepts input in the form of natural language/linguistic (very/quite/kinda/less) and converts it into a fuzzy membership value (range 0 to 1), processes it based on weight, cost, and benefit of existing criteria using Simple Additive Weighting (SAW), and combines the assessment results using Borda from 5 decision makers/business owners with their respective perceptions. So as to produce a final group decision. Where the final result obtained in the Borda method, that the alternative location A1 (A1 score is 6) gets the first priority to be business place establishment location, followed by A3 (A3 score is 5) in the second priority, and A2 (A2 score is 4) in the third priority/last.